Aggressive Thyroid Gland Carcinoma: A Case Series - James P Dworkin-Valenti; Esmael H Amjad; Noah Stern; Samba SR Bathula (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
In 2017 there were approximately 62000 new cases of thyroid cancer (TC) in the United States, with a death toll of less than 5%. This relatively low mortality rate is based on a grouping of all TC subtypes, which masks the small minority of patients with biologically aggressive tumors who have dismal prognoses for survival. The paper begins with a brief overview of TC variants relative to their alternative differential diagnostic characteristics, risk factors, and treatment options. We then proceed with presentations of 5 patients with different forms of aggressive TC, two of whom suffered from very rare collision tumor subtypes. Four of these individuals died of persistent disease, notwithstanding complex treatments with curative intent; the fifth patient suffers from metastatic disease and numerous postoperative morbidities. This case series highlights the significant shortcomings of current diagnostic and treatment ethodologies for aggressive thyroid gland tumors. We discuss our clinical experienceswith these patients, and we offer suggestions regarding methods that might facilitate early identification of aggressive TC and rational treatment decisions.